The effect of peer-to-peer health education on the perception of the smoking outcomes among adolescents in Kuching, Sarawak, 2007 - Jeffery, anak Stephen (Universiti Malaysia Sarawak (UNIMAS), 2009)
The main objective of the study was to examine whether the peer-to-peer health education was effective in changing the perception of the smoking outcomes among local adolescents in Kuching Sarawak. Nonparametric analyses of the scores showed that the peer-to-peer health education significantly changed the smoking outcomes perception among the participants in the intervention group (Wilcoxon Signed Rank test, p< .05) with significant change in the scale scores observed among the males (Wilcoxon Signed Rank test, p < .05). These modest findings lend credence that peer-to-peer health education is effective in changing the smoking outcomes perception among local adolescents with diverse cultural background.